A novel ligand-independent peptide inhibitor of TREM-1 suppresses tumor growth in human lung cancer xenografts and prolongs survival of mice with lipopolysaccharide-induced septic shock - Sigalov, Alexander B. (2014)
Triggering receptor expressed on myeloid cells-1 (TREM-1) amplifies the inflammatory response and plays a role in cancer and sepsis. Inhibition of TREM-1 by short hairpin RNA (shRNA) in macrophages suppresses cancer cell invasion in vitro. In the clinical setting, high levels of TREM-1 expression on tumor-associated macrophages are associated with cancer recurrence and poor survival of patients with non-small cell lung cancer (NSCLC). TREM-1 upregulation on peritoneal neutrophils has been found in human sepsis patients and in mice with experimental lipopolysaccharide (LPS)-induced septic shock. However, the precise function of TREM-1 and the nature of its ligand are not yet known. In this study, we used the signaling chain homooligomerization (SCHOOL) model of immune signaling to design a novel, ligand-independent peptide-based TREM-1 inhibitor and demonstrated that this peptide specifically silences TREM-1 signaling in vitro and in vivo. Utilizing two human lung tumor xenograft nude mouse models (H292 and A549) and mice with LPS-induced sepsis, we show for the first time that blockade of TREM-1 function using non-toxic and non-immunogenic SCHOOL peptide inhibitors: 1) delays tumor growth in xenograft models of human NSCLC, 2) prolongs survival of mice with LPS-induced septic shock, and 3) substantially decreases cytokine production in vitro and in vivo. In addition, targeted delivery of SCHOOL peptides to macrophages utilizing lipoprotein-mimicking nanoparticles significantly increased peptide half-life and dosage efficacy. Together, the results suggest that ligand-independent modulation of TREM-1 function using small synthetic peptides might be a suitable treatment for sepsis and NSCLC and possibly other types of inflammation-associated disorders.